2017
DOI: 10.1002/qua.25536
|View full text |Cite
|
Sign up to set email alerts
|

Design of zinc porphyrin‐perylene diimide donor‐bridge‐acceptor chromophores for large second‐order nonlinear optical response: A theoretical exploration

Abstract: The electronic structures and second‐order nonlinear optical (NLO) properties of a series of zinc porphyrin (ZnP)‐perylene diimide (PDI) donor‐bridge‐acceptor (D‐π‐A) molecules have been investigated using density functional theory (DFT) and time‐dependent DFT (TDDFT). The results show that these compounds possess excellent second‐order NLO properties and large static first hyperpolarizabilities (β0) values on the order of 103 – 104 esu−30. A DFT benchmark calculation of β0 value was first performed, confirmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…[10][11][12][13][14][15][16] What's more, to further improve the nonlinear optical properties, third-order nonlinear optical materials could increase the optical absorption intensity and broaden the light absorption range. [17][18][19][20][21] Meanwhile, due to their one-step method, high yield, generally stable products, and easy product purification, [2+2] click reactions have attracted much attention. Moreover, formal [2+2] cycloaddition-cycloreversion reactions can be combined with click chemical reagents (tetracyanoethylene (TCNE), 7,7,8,8-tetracyanoquinodimethane (TCNQ) and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ)) to prepare a series of nonplanar, p-conjugated, donor-acceptor chromophores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16] What's more, to further improve the nonlinear optical properties, third-order nonlinear optical materials could increase the optical absorption intensity and broaden the light absorption range. [17][18][19][20][21] Meanwhile, due to their one-step method, high yield, generally stable products, and easy product purification, [2+2] click reactions have attracted much attention. Moreover, formal [2+2] cycloaddition-cycloreversion reactions can be combined with click chemical reagents (tetracyanoethylene (TCNE), 7,7,8,8-tetracyanoquinodimethane (TCNQ) and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ)) to prepare a series of nonplanar, p-conjugated, donor-acceptor chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…10–16 What's more, to further improve the nonlinear optical properties, third-order nonlinear optical materials could increase the optical absorption intensity and broaden the light absorption range. 17–21…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, due to the structural adjustability, unique electronic and photophysical properties of porphyrins, porphyrins have broad application in various areas and good prospects ( Zhang et al, 2018 ; Chen et al, 2020 ; Asghar et al, 2021 ; Liu and Cheng, 2021 ). Particularly, the NLO performance of porphyrins could be improved by the flexible modification of peripheral substituents or the hybridization with other materials ( Zawadzka et al, 2013 ; Woller et al, 2016 ; Hu et al, 2018 ; Biswal et al, 2019 ; Samal et al, 2019 ; Liu J. L. et al, 2020 ; Liu Z. et al, 2020 ; Liu and Cheng, 2021 ; Ramasamy et al, 2022 ). However, previous research indicated the self-aggregate behavior of porphyrins could lead to the formation of large macro-scale and fractal structures, causing a negative impact in the development of NLO devices in practice ( Kalachyova et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work we also have demonstrated the accuracy and efficiency of this optimal tuning approach served as a reliable theoretical tool for a series of molecular properties. For example, through applying the optimally-tuned long-range corrected functionals, significant improvement is found for the prediction of the IPs, EAs and transport gap of πconjugated thiophene-based oligomers and polymers [38,50], nucleobase clusters [28], organic molecular crystals [29,51]; hyperpolarizabilities of 'push-pull' systems [52,53], and excitation energies of various organic fluorescence molecules [54][55][56][57]. Since the research of CNTs has rapidly become a hotspot in both academic and industry, there is still lack of a theoretical method that can provide quantitative prediction of properties of CNTs but with relatively low computational cost.…”
Section: Introductionmentioning
confidence: 99%